Systems of Ichthyonyms in the Tatar and Tuvan Languages - Galimova, Olga N. (The New Research of Tuva, 2025)
This article addresses, for the first time, the ichthyonyms of the Tatar and Tuvan languages from a comparative perspective. It has been established that the systems of ichthyonyms in the Tatar and Tuvan languages exhibit more distinctions than commonalities. Groups of names common to both Tatar and Tuvan languages (10 names) as well as language-specific names (with the greatest number of terms) have been identified. Six names, relating to the Proto-Turkic lexicon, are characterized by identical semantics or minor differences in meaning.Proposed are schematic models of possible semantic development of individual words, demonstrating shifts in meaning from concrete to general or from general to concrete. The specific features of the ichthyonymic systems in the studied languages have formed under the influence of linguistic and extralinguistic factors, including the fish habitat area, the uniqueness of the worldviews of the peoples, and the peculiarities of language development. The Tuvan language is characterized by ichthyonyms as euphemisms, reflecting the special attitude of the people toward fish.Generic components in the formation of ichthyonyms have been identified (two in Tatar, five in Tuvan), three of which are unique to Tuvan. A distinct group of specific terms consists of names for fish fry, which are represented in greater detail in Tuvan — primarily related to the more significant role of fish in the lives of Tuvan language speakers.Both Tatar and Tuvan languages have developed age-based names for five fish species; among them, names for different age groups of ide (Leuciscus) are used in both languages. It is noted that commonality manifests within specificity: the identified model for forming some dialectal names for fish fry in the studied languages indicates similarity in nomination.
Keywords: Tatar language; Tuvan language; Turkic language; ichthyonym; zoonym; semantic development; generic component